Tubercular Sialadenitis: A rare case report - Jabo, Alain; Afodun, Adam Moyosore; Mukangendo, Mecthilde; Kayitesi, Isabelle; Eze, Daniel Ejike; Uwimana, Lowami; Ganza, Jules; Quadri, Khadijah Kofoworola (Journal of Biomedical Sciences, 2024)
Background: Tubercular sialadenitis is an uncommon condition of extrapulmonary tuberculosis. It is responsible for fatal infections and ailments caused by Mycobacterium Tuberculosis. Due to diverse non-specific symptoms, it is often misdiagnosed as a form of parotid gland neoplasm. This diagnostic dilemma poses a challenge to medics, especially in a low-income setting of a developing country. Case presentation: We discuss a case of parotid salivary tuberculosis in a 25-year-old man who was scanned via a high-frequency 7.0 MHz transduced ultrasound scan and later verified histologically. On examination, bilateral submandibular and parotid bulges along the lateral neck region with marked lymphadenopathy were found. Sonography diagnosed him with a case of submandibular gland tuberculosis and confirmed bacteriologically by mycobacterial culture. Conclusion: Staining for AFB, biopsy and culture studies are necessary and recommended. Establishing a cure requires high awareness, suspicion and early diagnosis.